Automaticity of Word Reading: Evidence From the Semantic Stroop Paradigm. (October 2014) - Augustinova, Maria; Ferrand, Ludovic
Various lines of research have independently reported that different interventions reduce or even eliminate Stroop interference. Because such findings have been interpreted as evidence that word reading can be prevented and/or controlled, these lines of research challenge the widespread automatic view of word reading. This article provides methodological and empirical arguments explaining why such conclusions might not be warranted and summarizes direct empirical evidence showing that interventions used in past studies have not yet been found to prevent or impose any control over word reading in the Stroop task. The main conclusion of this article is that the processes involved in word reading might (still) be considered automatic.